Penggunaan Metode Preemptive Goal Programming Untuk Optimalisasi Produktivitas Tanaman Padi di Kota Pariaman - Triana Triana; Yusmet Rizal (Journal of Mathematics UNP, 2023)
Pariaman City is a city in West Sumatra which contributes to agriculture, especially rice. For this reason, rice production must be increased by paying attention to good management so as to increase the amount of rice production. This applied research aims to minimize the objectives of each constraint function encountered so that optimal rice production results can be obtained using the method approach preemptive goal programming. The constraints given are the use of seeds, the use of urea and NPK fertilizers, the use of pesticides, production yields and production values. Of the six targets considered, based on the results of the analysis, it shows that four targets have been met, namely the targets of maximizing production yields and production value and minimizing the use of urea and NPK fertilizers. In order to achieve this target, it is necessary to add 1.582 single varieties per hectare